Diurnal timing of physical activity in relation to obesity and diabetes in the German National Cohort (NAKO) - Stein, Michael; Weber, Andrea; Bamberg, Fabian; Baurecht, Hansjörg; Berger, Klaus; Bohmann, Patricia; Brenner, Hermann; Brummer, Julian; Dörr, Marcus; Fischer, Beate; Gastell, Sylvia; Greiser, Karin Halina; et al. (International journal of obesity, 2025)
Physical activity supports weight regulation and metabolic health, but its timing in relation to obesity and diabetes remains unclear. We aimed to assess the diurnal timing of physical activity and its association with obesity and diabetes.